Optical pH sensor based on polyelectrolyte complex (PEC) pectin-chitosan/methanol anthocyanin extract of Catharanthus roseus for a new optical urea biosensor development - EKA SAFITRI; KHAIRI SUHUD; NAZARUDDIN NAZARUDDIN; BINAWATI GINTING; SUSILAWATI SUSILAWATI; SITTI SALEHA; MURNIANA MURNIANA; SALSABILLA LATANSA NAZARUDDIN; NURHAYATI NURHAYATI (Universitas Syiah Kuala, 2021)
Construction of optical pH sensor as a new platform optical urea biosensor based on polyelectrolyte complex (PEC) pectin-chitosan membrane and total phenolic (anthocyanin) of Tapak Dara flower (Catharanthus roseus) has been successfully carried out. The anthocyanin was extracted by a maceration method for 72 hours using methanol, and a total extract yield was 21.56% or 1.803 mg/L. Flavonoid and phenol tests showed positive results indicated by the formation of red and black colours. The anthocyanins showed maximum absorption at 578 nm for phosphate buffer and 575 nm for tris HCl buffer solution. The sensor fabrication was performed using a mixture of pectin and chitosan solutions with a ratio of 3:7. The anthocyanin was mixed into the solution with various concentrations. The sensor has an optimum sensitivity at the anthocyanin concentration of 0.05 mg/L (phosphate buffer) in the pH range of 7.0-9.5 and 0.025 mg/L (Tris HCl buffer) with a narrower pH range of 6.0-7.5. This sensor produced higher sensitivity, a wider linear range, and good linearity when it was exposed in 0.03M PBS. Reproducibility test with a relative standard deviation percentage (% RSD) was 9.20. The sensor showed a stable response after 5 minutes exposed to PBS solution, and it can be used to measure pH within the 20th day. The optimized optical pH sensor has been successfully developed as a urea optical biosensor by immobilizing urease on its surface. The biosensor showed a linear response in a series of 10-1-10-10 M urea concentrations and has good linearity.